The Implementation Of Digital Attendance In Improving Civil Servant Discipline: A Case Study At Bkpsdm Bolaang Mongondow Timur - Rilke Afni Johannes; Moh. Rezhah Mamonto; Yanto Modeong; Agus Kristianto Djajusman (Publikasi Indonesia, 2025)
This study aims to analyse the effectiveness of implementing a digital attendance system in improving the state civil apparatus (ASN) discipline within the Personnel and Human Resources Development Agency (BKPSDM) of East Bolaang Mongondow Regency. This study uses a descriptive qualitative approach with a case study method and data triangulation through documentation of employee attendance, results of leadership interviews, and questionnaires to ASN. The results showed that the digital attendance system based on fingerprint technology and the SIADAB application (Boltim ASN Digital Attendance System) positively impacted ASN discipline. Attendance data shows a trend of high attendance consistency, while questionnaire respondents showed an outstanding level of acceptance of this system. In addition to increasing transparency and accountability, this system supports a more efficient and data-driven personnel management process. However, some challenges remain, such as limited infrastructure and technical constraints in the early stages of implementation. This study recommends strengthening training, developing an integrated system, and continuous managerial support to ensure the sustainability of digital innovation in ASN discipline management.